2020
DOI: 10.1259/bjrcr.20190125
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sarcoidosis masquerading as metastatic cervical cancer: a pitfall in CT scans and positron emission tomography (PET)

Abstract: Sarcoidosis has been associated with co-existing malignancies in several organs, including the breast and thyroid gland as well as lymphomas. However, the occurrence of sarcoidosis with cervical cancer is rare with only nine previous cases reported in the published literature. We present a case of pulmonary sarcoidosis imitating mediastinal lymph node metastases on the staging CT scan and positron emission tomography imaging. The presence of thoracic lymphadenopathy without any pelvic lymphadenopathy prompted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…On contrary, in another cross-registry study of 555 danish sarcoidosis patients, no increase incidence of malignancy is found, although this might slightly be due to lack of power [54]. Although breast, thyroid cancers are the most common [11] sarcoidosis coexisting with various other cancers were reported in the literature [55].…”
Section: Malignancies Coexisting With Sarcoidosismentioning
confidence: 86%
See 1 more Smart Citation
“…On contrary, in another cross-registry study of 555 danish sarcoidosis patients, no increase incidence of malignancy is found, although this might slightly be due to lack of power [54]. Although breast, thyroid cancers are the most common [11] sarcoidosis coexisting with various other cancers were reported in the literature [55].…”
Section: Malignancies Coexisting With Sarcoidosismentioning
confidence: 86%
“…Bala et al reported a case of testicular sarcoidosis mimicking as testicular malignancy in a 49-year-old Indian male who also has coexisting PTC [58]. Although rare, a case of cervical cancer in a 31-year-old female presenting as cervical fungating polyp with thoracic lymphadenopathy and without pelvic and para-aortic lymph node involvement which on further workup confirmed sarcoidosis coexistence [55]. In conclusion, whenever a lymph node pattern that is not in correlation with the cancer is seen, diagnostic uncertainty arises.…”
Section: Sarcoidosis With Other Cancersmentioning
confidence: 97%
“…[ 20 ] However, this mode of participation is not specific and can be found in Hodgkin’s lymphoma, especially the nodularsclerosis type. [ 21 , 22 ] In addition, parenchymal presentations and the age at onset of both also overlap. Moreover, the treatments of sarcoidosis and Hodgkin’s lymphoma are very different.…”
Section: Discussionmentioning
confidence: 99%